Recent advances in polymeric biomaterials-based gene delivery for cartilage repair - Yang, Ran (Bioact Mater, 2020)
Untreated articular cartilage damage normally results in osteoarthritis and even disability that affects millions of people. However, both the existing surgical treatment and tissue engineering approaches are unable to regenerate the original structures of articular cartilage durably, and new strategies for integrative cartilage repair are needed. Gene therapy provides local production of therapeutic factors, especially guided by biomaterials can minimize the diffusion and loss of the genes or gene complexes, achieve accurate spatiotemporally release of gene products, thus provideing long-term treatment for cartilage repair. The widespread application of gene therapy requires the development of safe and effective gene delivery vectors and supportive gene-activated matrices. Among them, polymeric biomaterials are particularly attractive due to their tunable physiochemical properties, as well as excellent adaptive performance. This paper reviews the recent advances in polymeric biomaterial-guided gene delivery for cartilage repair, with an emphasis on the important role of polymeric biomaterials in delivery systems.